Crystal, ferromagnetism, and magnetoresistance with sign reversal in a EuAgP semiconductor - Qian Zhao; Kaitong Sun; Si Wu; Hai-Feng Li (Journal of Materiomics, 2025)
We synthesized the ferromagnetic EuAgP semiconductor and conducted a comprehensive study of its crystalline, magnetic, heat capacity, band gap, and magnetoresistance properties. Our investigation utilized a combination of X-ray diffraction, optical, and PPMS DynaCool measurements. EuAgP adopts a hexagonal structure with the P63/mmc space group. As the temperature decreases, it undergoes a magnetic phase transition from high-temperature paramagnetism to low-temperature ferromagnetism. We determined the ferromagnetic transition temperature to be TC = 16.45(1) K by fitting the measured magnetic susceptibility using a Curie-Weiss law. Heat capacity analysis of EuAgP considered contributions from electrons, phonons, and magnons, revealing η = 0.03 J/(mol·K2), indicative of semiconducting behavior. Additionally, we calculated a band gap of ∼1.324(4) eV based on absorption spectrum measurements. The resistivity versus temperature of EuAgP measured in the absence of an applied magnetic field shows a pronounced peak around TC, which diminishes rapidly with increasing applied magnetic fields, ranging from 1 T to 14 T. An intriguing phenomenon emerges in the form of a distinct magnetoresistance transition, shifting from positive (e.g., 1.95% at 300 K and 14 T) to negative (e.g., −30.73% at 14.25 K and 14 T) as the temperature decreases. This behavior could be attributed to spin-disordered scattering.